Spontaneous Magnetic Fluctuations and Collisionless Regulation of Turbulence in the Earth S Magnetotail - Espinoza-Romo, C; Stepanova, M (IOP Publishing Ltd, 2022)
Among the fundamental and most challenging problems of laboratory, space, and astrophysical plasma physics is to understand the relaxation processes of nearly collisionless plasmas toward quasi-stationary states and the resultant states of electromagnetic plasma turbulence. Recently, it has been argued that solar wind plasma β and temperature anisotropy observations may be regulated by kinetic instabilities such as the ion cyclotron, mirror, electron cyclotron, and firehose instabilities; and it has been argued that magnetic fluctuation observations are consistent with the predictions of the fluctuation-dissipation theorem, even far below the kinetic instability thresholds. Here, using in situ magnetic field and plasma measurements by the THEMIS satellite mission, we show that such regulation seems to occur also in the Earth s magnetotail plasma sheet at the ion and electron scales. Regardless of the clear differences between the solar wind and the magnetotail environments, our results indicate that spontaneous fluctuations and their collisionless regulation are fundamental features of space and astrophysical plasmas, thereby suggesting the processes is universal. © 2022. The Author(s). Published by the American Astronomical Society..